The Influence of Financial Ratios on Banking Financial Performance - Jarwani, Gunem; Sahri, Mustofa; Rohmah, Nisa Aulia; Nurlatifah, Rini (FEBI UIN Sunan Kalijaga, 2023)
This research aims to determine the influence of financial ratios on the financial performance of banking institutions. The selected sample is Bank Rakyat Indonesia for the observation period from 2019 to 2022. All financial data was obtained through Bank Rakyat Indonesia's annual reports. This study involves financial ratio variables such as CAR, NPL, BOPO, and LDR, while the financial performance variable utilizes ROA. Multiple linear regression analysis was employed for data analysis in this research, utilizing the SPSS software. The research findings indicate that CAR significantly affects Bank Rakyat Indonesia's ROA. However, the other variables do not demonstrate any significant impact on Bank Rakyat Indonesia's ROA